Adult patients with Eisenmenger syndrome report flying safely on commercial airlines. Issue 12 (12th December 2006) - Broberg, Craig S; Uebing, Anselm; Cuomo, Linda; Thein, Swee Lay; Papadopoulos, Michael G; Gatzoulis, Michael A
Abstract : Background: Despite fears of compromised oxygen delivery in patients with Eisenmenger syndrome during flight on commercial aircraft, a clinical study has shown no adverse effects, and many patients travel frequently. Methods: The air travel history over the past decade of 53 patients with Eisenmenger syndrome and 48 acyanotic patients was obtained. Patients listed all flights and destinations, and any major adverse event or symptoms, including, specifically, headache, palpitations, oedema or need for supplemental oxygen. For the patients with Eisenmenger syndrome, a full blood count, 6-minute walk test and p50 of the oxygen–haemoglobin dissociation curve were also obtained. Results: 1157 flights were reported evenly between the two groups. Thirteen patients with Eisenmenger syndrome reported no travel in the past 10 years (vs 4/48 acyanotic patients, p = 0.03), six of whom were told not to fly by healthcare providers. Of those who flew, the number and distance of flights was similar in both groups. No major adverse events were reported. One patient with Eisenmenger syndrome possibly had a transient ischaemic attack and a second patient needed supplemental oxygen when exposed to ambient cigarette smoke in flight. Other symptoms such as headache, palpitations and lower extremity oedema at the travel destination were reported with similar frequency in both groups. Patients with Eisenmenger syndrome had a raised p50 of the oxygen–haemoglobin dissociation curve (mean (SD) 29.4 (2.6) mm Hg vs 27 (3) mm Hg in laboratory controls, p<0.01). Conclusions: Patients with Eisenmenger syndrome report travelling frequently and safely on commercial airlines. Shifts in the oxygen–haemoglobin dissociation curve are likely to attenuate the effects of low oxygen tension. Patients with Eisenmenger syndrome should, nevertheless, be advised to avoid inactivity and dehydration as usual, but there is no justification for limiting air travel.